Payload Mass Identification of a Single-Link Flexible Arm Moving under Gravity: An Algebraic Identification Approach - Juan Carlos Cambera; Andres San-Millan; Vicente Feliu-Batlle (Shock and Vibration)
We deal with the online identification of the payload mass carried by a single-link flexible arm that moves on a vertical plane and therefore is affected by the gravity force. Specifically, we follow a frequency domain design methodology to develop an algebraic identifier. This identifier is capable of achieving robust and efficient mass estimates even in the presence of sensor noise. In order to highlight its performance, the proposed estimator is experimentally tested and compared with other classical methods in several situations that resemble the most typical operation of a manipulator.